The effect of utilizing mobile on developing English writing skill: A case study at University Of Baghdad - Lafta Jassim, Lina; Dzakiria, Hisham (Opción, 2019)
The objectives of this study are to improving Iraqi EFL students' writing skills via a quantitative method. The researcher used tests and observation to collect his data during conducting this experience. The findings showed that mobile phones can successfully and easily be implemented as an instructive aid to teach writing skills because mobile phones motivate students for learning writing skills. In conclusion, this study offered some pedagogical implications of using mobile as an educational tool to develop students’ writing skills.